The Concept of Patah Titi: The Problem of Inheritance and Its Solution in Aceh Tengah - Fauzi, Fauzi (Studia Islamika, 2019)
This article examines the inheritance issue of patah titi practiced by the people of Aceh Tengah. Patah titi is a state in which one of the aṣḥāb al-furūḍ (obligatory sharers or primary heirs) loses linkage (due to death) to muwārith (the deceased). This study used descriptive analysis and drew upon legal pluralism, which considers the interaction between state laws, customary laws, and religious laws in resolving a case. The findings show that inheritance distribution is implemented in three steps: first, the heir inherits nothing due to the legal consequences of patah titi; second, the heir receives inheritance because they are considered a badl (substitution) of the predeceased heir; third, the heir receives hibah (gift). The last two steps in the settlement of patah titi are derived from various sources, including the Compilation of Islamic Law (KHI), customary law, and the universal values of Islamic law, which consider principles of equity, humanity and child protection.